2008
DOI: 10.1111/j.1467-937x.2007.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Contracts in the Video Rental Industry

Abstract: A large body of theoretical work has explored the channels through which vertical contracts can induce efficiency improvements. However, it is also important to study vertical contracts empirically in order to gain insight into the relative size of different types of efficiency gains. In this paper, I empirically analyse a contractual innovation in the vertically separated video rental industry. Prior to 1998, video stores obtained inventory from movie distributors using simple linear-pricing contracts. In 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(97 citation statements)
references
References 41 publications
3
93
0
1
Order By: Relevance
“…In economics, several papers have studied revenue sharing contracts in the video rental industry. Mortimer (2008), for example, analyzes fixed-price vs. revenue sharing contracts between distributors and retailers using a structural equation econometric approach. Her results indicate that both downstream and upstream firms" profits for popular titles increase by 10% under revenue sharing contracts and consumers are also generally better off.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In economics, several papers have studied revenue sharing contracts in the video rental industry. Mortimer (2008), for example, analyzes fixed-price vs. revenue sharing contracts between distributors and retailers using a structural equation econometric approach. Her results indicate that both downstream and upstream firms" profits for popular titles increase by 10% under revenue sharing contracts and consumers are also generally better off.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The retailer then determines a self-interest replenishment quantity (or a stocking factor) and/or retail price (Cachon and Lariviere, 2005;Gerchak et al, 2006;Van der Veen and Venugopal, 2005;Chauhan and Proth, 2005;Koulamas, 2006;Yao et al, 2008aYao et al, , 2008b. Such setting with somewhat variation is widely applied in the video rentals (Dana and Spier, 2001;Mortimer, 2008;Cachon and Lariviere, 2005;Gerchak et al, 2006;Van der Veen and Venugopal, 2005) and the internet content services (Foros et al, 2009). The non-consigned R-S arrangement is also an effective mechanism for collaborative new product development in intercompany alliances (Bhaskaran and Krishnan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We assume the vendor is a price-setting firm who sells the one-of-a-kind product in the market through the exclusive channel, and the demand is price-sensitive. While inspired by e-commerce practices, revenue sharing is also widely adopted in a variety of industries, including the video rentals (e.g., Dana and Spier, 2001;Mortimer, 2008;Cachon and Lariviere, 2005) and the retailing with consignment contracting (Coughlan et al, 2001;Turcsik, 2002). Other revenue-sharing examples can be found in the mobile networks with independent content providers (Foros et al, 2009), the assembly systems with vendor-managed inventory (Gerchak and Wang, 2004), and the chain stores with franchising arrangement, e.g., fast-food, hotel, automobile rentals, and gasoline dealerships (Lal, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A success story of Blockbuster Inc. is a famous example to show the potential of this contract. According to Mortimer (Mortimer, 2008), video rental stores with a revenue-sharing contract show 10% higher profits than those without a revenue-sharing contract. As such, a revenuesharing contract has been widely used in several industries such as video rental industry, franchise industry and online retailing (Qin and Yang, 2008;Wang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cachon and Lariviere (2005) conducted an extensive analysis and concluded that a revenue-sharing contract coordinates the supply chain in various settings and has a lot of strengths. Mortimer (2008) examined the video-rental industry and shows that a revenue-sharing contract plays an important role in coordinating the supply chain. Yao et al (2008) compared two contracts considering price-setting issue.…”
Section: Introductionmentioning
confidence: 99%